Edukasi Stunting sebagai Upaya Pencegahan Dini di SMA IT Imam Syafi'i (IMSYA) Kota Pekanbaru - Darmadi, Darmadi; Herlina, Sara; Rizal, Yose; Ayuningtias, Ratih (Penerbit Widina, Widina Media Utama, 2024)
Stunting is a growth disorder characterized by a toddler's height being shorter than that of children his age due to chronic malnutrition. Several factors that cause stunting include the family's economic status, nutritional intake of pregnant women, and lack of providing appropriate food to toddlers. The aim of this service is to measure students' understanding regarding stunting and the factors that cause it. The method used is counseling using lecture methods, question and answer discussions and pre-test and post-test questionnaires. Based on the results of a questionnaire to 45 respondents before being given counseling, it showed that the majority of students did not have adequate knowledge about stunting. After being given education, for 60 minutes by means of counseling, the understanding of IMSYA IT High School students and girls increased as shown by the results before the pre-test and after the post-test. This education succeeded in increasing students' awareness of the importance of preventing stunting through improving nutrition from an early age. Apart from that, Hb examination also provides an overview of students' health status related to anemia which can be one of the causes of stunting. Based on the counseling that has been given, it is hoped that school teachers in particular will be given detailed education, so that this program can run smoothly and can be implemented more widely in order to reduce the number of stunting incidents in the future.ABSTRAKStunting adalah gangguan pertumbuhan yang ditandai dengan tinggi badan balita yang lebih pendek dibandingkan anak seusianya akibat kekurangan gizi kronis. Beberapa faktor sebagai penyebab stunting diantaranya status ekonomi keluarga, asupan gizi ibu hamil, dan kurangnya pemberian makanan yang tepat pada balita. Tujuan pengabdian ini untuk mengukur pemahaman siswa terkait stunting dan faktor-faktor penyebabnya. Metode yang digunakan adalah penyuluhan dengan metode ceramah, diskusi tanya jawab dan kuesioner pre-test dan post-test. Berdasarkan hasil kuesioner terhadap 45 responden sebelum diberi penyuluhan menunjukkan sebagian besar siswa belum memiliki pengetahuan yang memadai tentang stunting. Setelah diberikan edukasi, selama 60 menit dengan cara penyuluhan, pemahaman siswa dan siswi SMA IT IMSYA meningkat yang ditunjukkan dari hasil sebelum pretes dan setelah postes. Edukasi ini berhasil meningkatkan kesadaran siswa terhadap pentingnya pencegahan stunting melalui perbaikan gizi sejak dini. Selain itu, pemeriksaan Hb juga memberikan gambaran status kesehatan siswa terkait anemia yang dapat menjadi salah satu penyebab stunting. Berdasarkan penyuluhan yang telah diberikan diharapkan kepada khususnya guru sekolah diberi edukasi secara detail, sehingga program ini dapat berjalan dengan lancar dan dapat diimplementasikan lebih luas guna menekan angka kejadian stunting di masa mendatang.